Type 1 diabetes mellitus effects on mitochondrial function - Carvalho, Tiago Filipe Cruz (2013)
Despite type 1 diabetes mellitus being more rare, it has an autoimmune origin and appears early in life, greatly affecting its quality. With the aim of better understand the molecular mechanisms underlying the observed phenotypic alterations in the skeletal muscle from diabetic patients, it was planned an experimental protocol using 20 Wistar rats 8 weeks old, randomly divided in two groups (n=10). The animals from one group were injected with 60mg/Kg of streptozotocin (STZ), while the others were injected with vehicle buffer. Four months after STZ injection, rats were confirmed as diabetic, considering hyperglycemia and body weight loss. After animals sacrifice, gastrocnemius muscles were excised and used for mitochondria subpopulations (subsarcolemmal (SS) and intermyofibrillar (IMF)) isolation. mtDNA-to-muscle mass ratio suggest an increased biogenesis of SS mitochondria in the STZ animals, paralleled by a decreased protein content per mitochondrion, in opposite to the observed in IMF mitochondria. The BN-PAGE profile revealed a slight difference of the oxidative phosphorylation complexes organization between mitochondrial subpopulations, apparently not affected by STZ administration. Mitochondrial proteolysis analysis, evaluated through zymography, revealed two proteases with molecular weights around 15 and 25 KDa, with the smaller one presenting STZinduced significant decreased activity in IMF mitochondria. A similar behavior was observed for paraplegin, a subunit of m- AAA proteolytic system, and mitofilin, a protein involved in cristae organization. Interestingly, these protein levels were higher in SS mitochondria from diabetic animals. With this work it was verified that subsarcolemmal mitochondria are not so affected by STZ administration as IMF mitochondria. The decreased activity of the protein quality control system seems to be associated with the morphological and biochemical alterations observed in the mitochondria interspersed in fibrils.